Amino-acid and biochemical composition of whole body and molt of the Indian white shrimp - Dayal, J Syama; Ali, S Ahamad; Sarada, C (Indian Journal of Fisheries, 2011)
The amino acid and biochemical composition of molt (exuvia) and whole body of the shrimp, Fenneropenaeus indicus were analysed along with morphometric relations. The wet weight of exuvia (0.22 Â± 0.07 g) is nearly 4.8% of the whole shrimp weight (4.50 Â± 1.42 g). The goodness fit statistics R2 revealed highly significant relationship in weights of wet exuvia- wet shrimp, dry exuvia- wet shrimp and dry exuvia- dry shrimp with values 0.90, 0.89 and 0.88, respectively indicating that more than 88% of variation of the data explained by the models. The crude protein and crude fat contents of whole shrimp expressed on dry matter basis were 3-5 times higher than those found in exuvia. However, the exuvia of the shrimp had more than twice the dry matter and about four times ash contents when compared to that of whole shrimp body. The amino-acid composition of the whole shrimp body and the exuvia expressed on dry matter basis were 63.37 and 11.94 per cent, respectively. Glutamic acid, leucine and aspartic acids in the whole shrimp and glutamic acid, glycine and alanine in the exuvia were the predominant amino acids.